Rapid Emergence of Multidrug-Resistance among Gram Negative Isolates at a Tertiary Pediatric and Maternity Hospital in Ulaanbaatar, Mongolia - Susanna Felsenstein; Sarantsetseg Bira; Narangerel Altanmircheg; Enkhtur Shonkuuz; Ariuntuya Ochirpurev; David Warburton (University Library System, University of Pittsburgh, 2020)
Introduction: Information on microbiological and susceptibility profiles of clinical isolates in Mongolia is scarce, hampering infection control and clinical care. Methods: Species and resistance profiles of 6334 clinical gram negative isolates, collected at Mongolia's National Center for Maternal and Child Health between 2014 and 2017 were analyzed. Results: Annual proportion of multidrug-resistance among E. coli and Enterobacter isolates increased from 2.8% to 16.6% and 3.5% to 22.6% respectively; Klebsiella isolates exhibiting susceptibilities suggestive of extended spectrum beta-lactamase (ESBL) production from 73% to 94%. By 2017, 60.6% of Klebsiella isolates were multidrug-resistant, most originated from intensive care wards.  Enterobacteriaceae exhibiting susceptibility patterns suggestive of ESBL production and multidrug-resistant organisms were common and their incidence increased rapidly. Conclusion: These findings will serve to build strategies to strengthen microbiological surveillance, diagnostics and infection control; and to develop empiric therapy and stewardship recommendations for Mongolia's largest Children's and Maternity hospital.